Dual adhesive unipolar polysaccharides synthesized by overlapping biosynthetic pathways in Agrobacterium tumefaciens. Issue 5 (4th March 2022) - Onyeziri, Maureen C.; Hardy, Gail G.; Natarajan, Ramya; Xu, Jing; Reynolds, Ian P.; Kim, Jinwoo; Merritt, Peter M.; Danhorn, Thomas; Hibbing, Michael E.; Weisberg, Alexandra J.; Chang, Jeff H.; Fuqua, Clay
Abstract: Agrobacterium tumefaciens is a member of the Alphaproteobacteria that pathogenises plants and associates with biotic and abiotic surfaces via a single cellular pole. A. tumefaciens produces the u nip olar p olysaccharide (UPP) at the site of surface contact. UPP production is normally surface‐contact inducible, but elevated levels of the second messenger cyclic diguanylate monophosphate (cdGMP) bypass this requirement. Multiple lines of evidence suggest that the UPP has a central polysaccharide component. Using an A. tumefaciens derivative with elevated cdGMP and mutationally disabled for other dispensable polysaccharides, a series of related genetic screens have identified a large number of genes involved in UPP biosynthesis, most of which are Wzx‐Wzy‐type polysaccharide biosynthetic components. Extensive analyses of UPP production in these mutants have revealed that the UPP is composed of two genetically, chemically, and spatially discrete forms of polysaccharide, and that each requires a specific Wzy‐type polymerase. Other important biosynthetic, processing, and regulatory functions for UPP production are also revealed, some of which are common to both polysaccharides, and a subset of which are specific to each type. Many of the UPP genes identified are conserved among diverse rhizobia, whereas others are more lineage specific. Abstract : The plant pathogen Agrobacterium tumefaciens produces an adhesive polysaccharide structure at one end of the rod‐shaped cell that enables surface attachment and biofilm formation. This unipolar polysaccharide (UPP) is produced on biotic and abiotic surfaces and can be observed using polysaccharide‐specific labeling dyes as well as by fluorescence and electron microscopy. In this study, we define the set of genes required for UPP biosynthesis and find the structure to be composed of two distinct polysaccharides.